EKSISTENSI PENGGUNAAN BAHASA INDONESIA PADA BUDAYA “NONGKRONG” GENERASI MILENIAL - Dewi Kurnia Sari; Bagus Wahyu Setyawan (Jurnal Komposisi, 2021)
Indonesian is the identity and identity  of an Indonesian nation. Indonesian plays  an important role in all aspects of life. As time goes by, the world is growing. The shift in Indonesian vocabulary has both good and bad effects, causing the existence of the Indonesian  language  to  decline.  Not  only  that,  the  shift  in  one's  lifestyle  is  also increasingly different. In this day and age everyone wants a change, many people are now happy to be outside the home. One of the activities done outside the home is hanging out. Hang out perpetrators usually occur in young people or what is known as the millennial generation. The millennial generation is a group that has the same behavior, place or year of birth. Currently there is a hangout cultural phenomenon, where the current millennial generation often gathers with friends of the same generation or anyone just to brew a drink or taste food in a cafe.